Intestinal parasite infections in dogs affected by multicentric lymphoma and undergoing chemotherapy. (April 2019) - Cervone, Mario; Gavazza, Alessandra; Zbriger, Alina; Mancianti, Francesca; Perrucci, Stefania
Highlights: Intestinal parasites were evaluated in dogs with lymphoma and in control dogs. In dogs with high-grade multicentric lymphoma, protozoa infections were prevalent. Opportunistic protozoa were prevalent in lymphoma dogs undergoing chemotherapy. Results underline the need to monitor lymphoma dog patients for intestinal protozoa. Abstract: Prevalence and species composition of intestinal parasites were evaluated in dogs affected by high-grade multicentric lymphoma and undergoing chemotherapy and in control healthy dogs. Obtained data were statistically analyzed. The overall prevalence of intestinal parasite infections was 33.3%. In lymphoma dogs, the prevalence of protozoa infections (46.7%) was significantly higher (p < 0.05) than that of helminth infections (6.7%) and Giardia duodenalis, Cryptosporidium spp., Neospora caninum, Cystoisospora ohioensis -complex, Entamoeba sp. and Spirocerca lupi were identified. In the control group, only 3/15 dogs (20%) were found positive and no statistically significant differences emerged regarding helminth (hookworms and Toxocara canis ) and protozoa ( G. duodenalis ) infections. Results from this study may suggest a potential higher prevalence of opportunistic intestinal protozoa, including some potentially zoonotic species, in dogs affected by high-grade multicentric lymphoma, emphasizing the need to monitor lymphoma-affected dogs for these protozoa, especially those undergoing chemotherapy.